1989
DOI: 10.1192/bjp.154.1.58
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of Family Therapy v. a Relatives Group for Schizophrenia

Abstract: Schizophrenic patients living in high contact with relatives having high expressed emotion (EE) were recruited for a trial of social interventions. The patients were maintained on neuroleptic medication, while their families were randomly assigned to education plus family therapy or education plus a relatives group. Eleven out of 12 families accepted family therapy in the home, whereas only six out of 11 families were compliant with the relatives group. Non-compliance was associated with a poorer outcome for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
1
8

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(111 citation statements)
references
References 21 publications
2
100
1
8
Order By: Relevance
“…been recorded in studies of depression (Vaughn and Leff, 1976a), schizophrenia in Denmark and rural communities in India (Leff et al, 1989); these could offer a likely explanation for the low levels of EE recorded in the study presented here. Dare (1992) has shown that levels of EE in families with a conduct disordered or bulimic child are quite high when compared with relatives of anorexic children (see later), and we can look at the question of levels of EE in the light of our clinical knowledge of the families.…”
Section: -mentioning
confidence: 47%
See 1 more Smart Citation
“…been recorded in studies of depression (Vaughn and Leff, 1976a), schizophrenia in Denmark and rural communities in India (Leff et al, 1989); these could offer a likely explanation for the low levels of EE recorded in the study presented here. Dare (1992) has shown that levels of EE in families with a conduct disordered or bulimic child are quite high when compared with relatives of anorexic children (see later), and we can look at the question of levels of EE in the light of our clinical knowledge of the families.…”
Section: -mentioning
confidence: 47%
“…Kuipers and Bebbington (1988) therefore suggest that EE represents an aspect of ongoing family interaction, and similarly, Vaughn ( 1989) describes the EE index as an indicator of the emotional temperature of the family. A related question is that in some family intervention studies (Berkowitz et al, 1984;Leff et al, 1989) it has been shown that levels of EE can be altered in order to improve symptomatic outcome. I n these family intervention studies changes in levels of criticism but not Emotional Over-Involvement were achieved.…”
Section: Prognostic Value O F Ee and Changes In Ee During Therapymentioning
confidence: 99%
“…Em relação à intervenção testada, cinco ensaios foram classificados como de linha pragmáti-ca 49,50,51,56,57,58,61,62 . Quatro ensaios 52,53,54,59,60,65 foram classificados como comportamentais e dois 55,63,64 , como cognitivo-comportamentais.…”
Section: Diagnostic and Statistical Manual Of Mental Disorders Fourtunclassified
“…(2) Los beneficios obtenidos tras la intervención se mantienen en dos años de seguimiento, con un incremento de las recaídas si la intervención no es continuada (Fallón, 1985). (3) El rango menor de recaídas se asociaba a un mayor descenso en el nivel de EE (Hogarty, McEvoy, Munezt, DiBarry, Bartone, Cather, Cooley, Ulhrich, Cárter y Madonia, 1988;Tarrier et al , 1988;Leff et al , 1989). (4) Las intervenciones que incorporan programas educacionales y medidas profilácticas favorecen la reducción del estrés o tensión dentro del ámbito familiar (Tarrier, 1991).…”
Section: Intervenciones Familiares Orientadas a Reducir Los Altos íNdunclassified